1990
DOI: 10.1088/0031-9155/35/7/007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of bioheat transfer theories: measurement of temperature profiles around large artificial vessels in perfused tissue

Abstract: The verification of thermal models for use in hyperthermia treatment planning is essential. We investigated the heat transfer between a single vessel and the surrounding vascularised tissue, comparing the conventional bioheat transfer theory and the recently developed keff model using analytical and numerical methods. A plastic tube inserted into the tissue of an isolated perfused organ served as an artificial vessel. This enabled us to vary the blood flow in the vessel and in the tissue independently. The org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 107 publications
(55 citation statements)
references
References 9 publications
2
52
1
Order By: Relevance
“…Consistent in vivo estimation of conductivity is demonstrated in the measurements made in the rabbit thigh muscle. The results show small variations in tissue conductivity, with and without perfusion, and are in stark contrast to previous studies (18), where a maximum sixfold increase in apparent conductivity was attributed to perfusion.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Consistent in vivo estimation of conductivity is demonstrated in the measurements made in the rabbit thigh muscle. The results show small variations in tissue conductivity, with and without perfusion, and are in stark contrast to previous studies (18), where a maximum sixfold increase in apparent conductivity was attributed to perfusion.…”
Section: Discussioncontrasting
confidence: 99%
“…In the case where perfusion w b ϭ 0 and the heat source Q is an impulse in either 3D or 2D and in time, it can be shown that the resulting temperature on the plane orthogonal to the axis of the heat source is a 2D Gaussian distribution expanding at a rate proportional to k t , the conductivity. This notion has been used previously (12,18) to characterize the effects of perfusion. Specifically, it was assumed that both conductivity and perfusion influenced the expansion rate, and the notion of an effective conductivity measure, k eff , which captured information about both k t and w b , was coined:…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Song et al [1997] experimentally showed a quadratic dependence of k eff on f b in muscle confirming that the WJE for k eff was valid. However, our skin measurements were in agreement with other literature data showing a linear relationship between k eff and f b [Crezee and Lagendijk, 1990;Ducharme and Tikuisis, 1991;Crezee et al, 1994].…”
Section: Discussionsupporting
confidence: 92%